Pengembangan Kafah Learning Model untuk Meningkatkan Pemahaman Konsep Fluida Dinamis - A, Syahrial; Rokhmat, Joni; Ramdani, Agus; Hakim, Aliefman (Universitas Hamzanwadi, 2023)
This study aims to develop the Kafah Learning Model as an alternative to making learning meaningful. The research design uses a 4D model, namely define, design, develop, and disseminate. The Kafah Learning Model for Science developed is Dynamic Fluid Concepts (Airplane Lift). The data was collected with meaningful learning questionnaires and kafah concept understanding tests. The testing stage is the stage of knowing the influence of the Kafah Learning Model on understanding concepts in a kafah manner and knowing the meaningful learning response of prospective teachers. The increase in understanding of the concept is calculated based on the N-Gain and paired t-test. The results showed that the Kafah Learning Model for Dynamic Fluid Concepts (Airplane Lift) which was developed was valid and reliable, worthy of use in meaningful learning and influential in increasing the understanding of science concepts in kafah.